A Case of Primary Uterina Lymphoma Presenting with Bleeding, Pelvic Pain, and Dysmenorrhea - Lilian Yukari Miura; Miriam Anyury Daquin Maure; Monica Tessmann Zomer; Reitan Ribeiro; Teresa Cristina Santos Cavalcanti; William Kondo (Case Reports in Obstetrics and Gynecology)
Primary non-Hodgkin’s lymphoma (NHL) can arise from lymphatic cells located in solid organs (extranodal) and it accounts for 25 to 35% of all NHL. Primary lymphoma on the female genital tract (PLFGT) is a rare disease, comprising 0.2 to 1.1% of all extranodal lymphomas in the female population. In this paper, the authors report an extremely rare case of a 48-year-old woman who exhibited an abnormal uterine bleeding, pelvic pain, and dysmenorrhea history. The transvaginal ultrasound showed an anteverted uterus measuring 153 cm3 in volume, with intramural leiomyomas. She underwent a total laparoscopic hysterectomy with bilateral salpingectomy. The histologic evaluation of the specimen showed a follicular lymphoma with diffuse pattern in the endometrium. This report illustrates the difficulty in the diagnosis of primary lymphomas of the female genital tract.